PEMBELAJARAN MEMBACA PEMAHAMAN PADA SISWA KELAS V SD NEGERI 1 CIDEMPET KECAMATAN ARAHAN KABUPATEN INDRAMAYU - Muhafidin Muhafidin (Profesi Pendidikan Dasar, 2016)
This research is motivated by the ability of fifth grade students' reading comprehension is low, evidenced by the students do not understand and comprehend the content of reading, students had difficulty answering questions relating to the content of reading, as well as the average value of students still under KKM. This study aims to determine the effect of learning methods talk think write on the ability of reading comprehension folklore in class V SD Negeri 1 Cidempet of Arahan District of Indramayu Regency. This study was an experimental study. The population in this study were students of class V SD Negeri 1 Cidempet of Arahan District of Indramayu Regency totaling 22 students. The sampling technique used is total sampling where authors set into the sample population. So the study sample used is a fifth grade students of SD Negeri 1 Cidempet of Arahan District of Indramayu Regency totaling 20 students. Data collection techniques used is to write test. Data analysis techniques in this study is the normality test and test hypotheses (z test) is used to determine the effect of learning methods talk think write to the reading comprehension of folklore in class V SD Negeri 1 Cidempet of Arahan District of Indramayu Regency. Based on test results using a statistical hypothesis test obtained Z hit (7,458) Z daf (2.35), then thank Hi means that there are significant learning method talk think write to the reading comprehension of folklore in class V SD Negeri 1 Cidempet of Arahan District of Indramayu Regency. The conclusion of this study is the application of learning methods talk think write on the ability of reading comprehension folklore in class V SD Negeri 1 Cidempet of Arahan District of Indramayu Regency. Suggestions in this study is teachers can implement a wide variety of learning methods in the implementation of learning so that students are active in studying and understanding the concepts being taught, and teachers should use teaching methods talk think write to improve reading comprehension folklore.